2004
DOI: 10.1007/s00436-004-1188-3
|View full text |Cite
|
Sign up to set email alerts
|

Six Trypanosoma cruzi strains characterized by specific gene expression patterns

Abstract: The intracellular parasite Trypanosoma cruzi, the causative agent of Chagas disease, is known to comprise heterogeneous populations. One possibility to explain the obviously distinct phenotypes of different T. cruzi strains is differential expression of particular genes. This could result in environmental adaptations of the parasite within host organs, leading to distinct clinical symptoms. With the aim of identifying differentially expressed genes, we examined different T. cruzi strains by suppression subtrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…T. cruzi possesses four copies of TcOYE demonstrating the importance of this enzyme to parasite well-being. While differential expression of PGF 2α synthases has been reported in other studies (Andrade et al, 2008; Dost et al, 2004), they have failed to corroborate the relationship between PGF 2α synthase expression and drug resistance. A reason for this may be the presence of additional NADPH oxidoreductases from the cytochrome P-450 family in T. cruzi (Portal et al, 2008).…”
Section: 3 Lipid Metabolism and Eicosanoid Biosynthetic Pathways Imentioning
confidence: 67%
“…T. cruzi possesses four copies of TcOYE demonstrating the importance of this enzyme to parasite well-being. While differential expression of PGF 2α synthases has been reported in other studies (Andrade et al, 2008; Dost et al, 2004), they have failed to corroborate the relationship between PGF 2α synthase expression and drug resistance. A reason for this may be the presence of additional NADPH oxidoreductases from the cytochrome P-450 family in T. cruzi (Portal et al, 2008).…”
Section: 3 Lipid Metabolism and Eicosanoid Biosynthetic Pathways Imentioning
confidence: 67%
“…Natural populations of T. cruzi are very heterogeneous in biological, biochemical, immunological, and molecular features (Miles 2003;Dost et al 2004;Mathieu-Daudé et al 2007;Santos-Mallet et al 2008;Venegas et al 2010); consequently, different strains from endemic areas might be responsible for distinct clinical manifestations and chemotherapy response (Andrade 1999). In this context, previous works reported that T. cruzi strains produced different amounts of proteases, including the major cysteine protease named cruzipain (Fampa et al 2008(Fampa et al , 2010Gomes et al 2009;Kikuchi et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Group I is prevalent in the southern area of South America and is related to pathological outcomes of chronic CD, and group II is more confined to the Northern part of South America and Central America and involves the jungle cycle of infection mainly in animals as marsupials. So far, although a great deal of evidence is being accumulated to characterize the different clinical phenotypes of T. cruzi strains -as virulence factors,distinct gene/antigens expression, molecules associated with invasion of host tissue, etc -major basic and clinical research is necessary to elucidate different clinical outcomes in CD due to the specific characteristics of T. cruzi parasites 32,33 The data reported herein show our experience with CD and BMT in four health care centers from Argentina, and prove the relevance of monitoring reactivation or infection events along the evolution in BMT patients; the data also emphasize that CD is a controllable risk for patients undergoing BMT.…”
Section: Discussionmentioning
confidence: 99%